Assessment of efficiency and impacts of gillnets on fish conservation in a tropical freshwater fishery. Issue 2 (31st July 2016) - Silvano, Renato A.M.; Hallwass, Gustavo; Juras, Anastácio A.; Lopes, Priscila F.M.
Abstract: Gillnets are commonly used in tropical multi‐species fisheries and there is a need to investigate the comparative efficiency and impacts of this gear on fish populations and diversity. The efficiency and the impact of gillnets of distinct mesh sizes were compared in the Lower Tocantins River (Brazilian Amazon). Fish sampling was conducted in 12 floodplain lakes using gillnets of distinct mesh sizes and 345 fish landings were recorded. Indicators of gillnet efficiency were: (1) catch per unit of effort (CPUE) of total fish sampled; (2) CPUE of fish caught by fishers; (3) CPUE of commercial fish sampled; and (4) proportion of biomass of commercial fish sampled. Indicators of impact were: (1) the number of non‐commercial fish (by‐catch); (2) the proportion of fish above the length at first maturity; (3) mean fish size (length); (4) total number of fish species and of rare fish species caught. Gillnets of 8 cm mesh size showed a higher CPUE in fish samples and fish landings. This mesh size also showed reduced impacts (lower numbers of non‐commercial fish caught and higher proportion of adult fish). Gillnets of 6 cm mesh size caught a smaller proportion of adult fish, smaller fish, more species and more rare species. Therefore, intensive use of these gillnets could increase the risk of regional species extinctions and impair the provision of ecosystem services by target fish. Gillnets of 8 cm mesh size could improve fish catches while minimizing adverse effects of gillnet fishing. The practical management recommendation would be to replace the more damaging small mesh gillnets by gillnets with intermediate mesh size. This recommendation could simultaneously protect small‐sized rare species and larger fish, being broadly applicable to other small‐scale and multi‐species fisheries that use gillnets intensively in tropical countries with high fish diversity. Copyright © 2016 John Wiley & Sons, Ltd.